Primary Immunodeficiency Diseases : Definition, Diagnosis, and Management - Rezaei, Nima; Aghamohammadi, Asghar; Notarangelo, Luigi D. (Springer Berlin Heidelberg : Imprint: Springer, 2017)
Primary immunodeficiency diseases (PIDs) are a group of inborn disorders of the immune system, characterized by increased susceptibility to infections, autoimmunity, and cancers. Although PIDs were previously considered rare conditions, the number of diagnosed cases is growing rapidly, and about 300 different forms of PIDs have already been recognized. Nevertheless, because of inadequate medical awareness, misdiagnosis or late diagnosis occurs in a significant number of patients, leading to avoidable morbidity and mortality. The first edition of this practical reference textbook was widely welcomed by scientists and clinicians from around the world. This new edition has been extensively revised to reflect advances in knowledge and includes various PIDs not previously covered. For each disease, information is provided on definition, etiology, clinical manifestations, diagnosis, and management. Every effort has been made to ensure that, throughout, the text is easy to read and readily comprehensible. The book will represent an ideal resource for specialists when engaging in diagnosis, clinical decision-making, and treatment planning. It will also prove invaluable for doctors in training and other physicians and nurses who wish to learn more about PIDs.
Keywords: Medicine.; Human genetics.; Immunology.; Allergy.; Infectious diseases.; Pediatrics.; elektronické knihy; electronic books